1993
DOI: 10.1530/acta.0.1290188
|View full text |Cite
|
Sign up to set email alerts
|

Life with Turner's syndrome—a psychosocial report from 22 middle-aged women

Abstract: Life with Turner's syndrome-a psychosocial report from 22 middle-aged women. Acta Endocrinol 1993:129:188-94. ISSN 0001-5598 Twenty-two middle-aged women (median age 44.5 years) with Turner's syndrome were interviewed about family background, social identity, emotional development, relations, female identity, sexuality and reactions to the diagnosis, to evaluate how the condition has affected their lives and coping style. During the years preceding the diagnosis and hormonal replacement therapy (HRT) they ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 15 publications
6
53
0
2
Order By: Relevance
“…Also mentioned was how their diagnosis later interfered with dating, as some women were hesitant to enter into relationships out of fear of being rejected once their partners learned of their inability to reproduce. These findings are supported by Sylvén and colleagues' research study of 22 middle-aged women with TS, which revealed infertility as the most difficult and distressing consequence of their condition and acknowledged similar sentiments surrounding infertility and intimate relationships [Sylven et al 1993]. Given the lifelong sadness associated with infertility, creating a family environment that does not define a woman or a woman's successes by her ability to bear biological children could help girls and women with TS view themselves beyond their reproductive capacities.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Also mentioned was how their diagnosis later interfered with dating, as some women were hesitant to enter into relationships out of fear of being rejected once their partners learned of their inability to reproduce. These findings are supported by Sylvén and colleagues' research study of 22 middle-aged women with TS, which revealed infertility as the most difficult and distressing consequence of their condition and acknowledged similar sentiments surrounding infertility and intimate relationships [Sylven et al 1993]. Given the lifelong sadness associated with infertility, creating a family environment that does not define a woman or a woman's successes by her ability to bear biological children could help girls and women with TS view themselves beyond their reproductive capacities.…”
Section: Discussionmentioning
confidence: 60%
“…Physical features associated with a TS karyotype may include: ovarian failure with associated infertility, short stature, cardiovascular and renal malformations, hypertension, diabetes, hearing loss, skeletal abnormalities and neck webbing [Lippe 1991;Sybert 2001;Cunniff 2002;Elsheikh et al 2002]. Girls and women with TS generally have a normal range of cognitive abilities but may have learning difficulties, particularly related to nonverbal skills such as visual-spatial abilities, motor coordination, and mathematics [Skuse 1987;Sylven et al 1993;Saenger 1996;Lagrou et al 1998;van Borsel et al 1999;McCauley et al 2001;Ross 2001;Sybert 2001;Elsheikh et al 2002;Frias and Davenport, 2003].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations